Chapter Il complesso architettonico dei gesuati a Venezia - LENZO, Fulvio (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2020)
This paper aims at explaining exactly how the Jesuati slowly appropriated the Holy Name for themselves, visually incorporating it in their artistic creations. Through an exploration of the uses and practices of the supporters the cult of the Name of Jesus, such as Bernardino of Siena, and the similarly named Jesuiti, a more nuanced understanding of the Jesuati's own reception emerges.